Soft Tissue Cephalometric Analysis of Malay Orthodontic Patients (Funding work) - DR. YAHYA H. Y. ALFARRA; DR. KHOIRULZARIAH ISMAIL; DR. ANIS FARHAN KAMARUDDIN (International Journal of Pharma and Bio Sciences, 2018)
Soft tissue analysis plays a very important role in orthodontics where it aids in the diagnosis, treatment planning, improve treatment success and establish optimal facial harmony. The soft tissues are a major factor in determining the external facial appearance. The establishment of Holdaway analysis among Malay patient would further aid our understanding on Malay patient’s soft tissue profile. The aim of this study was to evaluate soft tissue measurements for a Malay sample population using Holdaway’s analysis. We also compared our soft tissue findings and the patients’ respective skeletal patterns. Cephalometric radiographs of 62 Malay female adult patients aged 18 to 40 years old who attended Orthodontic Specialist Clinic, Advanced Medical and Dental Institute, Universiti Sains Malaysia, Malaysia were traced and evaluated. Cephalometric landmarks were located according to Holdaway analysis. Nine linear and two angular measurements were produced on each radiograph. The results suggested that, the soft tissue measurements for the Malay females were different to that of the Holdaway norms, except for the soft tissue facial angle, upper lip curvature, and nose prominence, whilst the other measurements were larger than the Holdaway averages. The Malay female sample had pronounced convexity soft tissue facial profile, as well as deeper superior and inferior sulci, and thicker soft tissue chins than the Holdaway values. To conclude, the normal values of Holdaway soft tissue analysis for the Malay female adults were established for use in orthodontic practices in this population.